2023
DOI: 10.3390/cells12010184
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics Mechanism of Action on Immune Cells and Beneficial Effects on Human Health

Abstract: Immune cells and commensal microbes in the human intestine constantly communicate with and react to each other in a stable environment in order to maintain healthy immune activities. Immune system-microbiota cross-talk relies on a complex network of pathways that sustain the balance between immune tolerance and immunogenicity. Probiotic bacteria can interact and stimulate intestinal immune cells and commensal microflora to modulate specific immune functions and immune homeostasis. Growing evidence shows that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
103
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(105 citation statements)
references
References 280 publications
1
103
0
1
Order By: Relevance
“…In recent years, great progress was achieved in the study of the mechanisms of symbiosis between lactic acid bacteria and the host. Their main beneficial effects have been shown to include the regulation of the imbalance of the intestinal flora [ 42 ], the strengthening of the intestinal barrier functions [ 23 , 27 , 36 ], the maintenance of homeostasis [ 36 , 43 ], the regulation of the immune system [ 43 ], and the production of neurotransmitters (gut–brain axis) [ 44 ]. It has been also shown that the exopolysaccharide (EPS) produced by lactobacilli has the peculiar ability to modify the microbiota [ 45 ], and to improve the colonization and growth of intestinal bacteria by acting as a carbon source [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, great progress was achieved in the study of the mechanisms of symbiosis between lactic acid bacteria and the host. Their main beneficial effects have been shown to include the regulation of the imbalance of the intestinal flora [ 42 ], the strengthening of the intestinal barrier functions [ 23 , 27 , 36 ], the maintenance of homeostasis [ 36 , 43 ], the regulation of the immune system [ 43 ], and the production of neurotransmitters (gut–brain axis) [ 44 ]. It has been also shown that the exopolysaccharide (EPS) produced by lactobacilli has the peculiar ability to modify the microbiota [ 45 ], and to improve the colonization and growth of intestinal bacteria by acting as a carbon source [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that the intake of probiotic bacteria contributes to a proper intestinal functioning by maintaining the epithelial permeability, enhancing the mucous layer, increasing enterocyte turnover, stimulating the innate and adaptative immune response and restoring gut microbiota composition and activity [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, norepinephrine has been identified as a factor that increases proliferation of pathogens such as Escherichia coli , Yersinia enterocolitica , and Pseudomonas aeruginosa [ 145 ]. Deficiencies in catecholamine concentration might contribute to neurodegenerative diseases such as Alzheimer’s and Parkinson’s disorders and MDD [ 148 ]. The effect of probiotics on catecholamine metabolism was determined in animal models.…”
Section: Intestinal Microbiotamentioning
confidence: 99%
“…Probiotics have the capacity to induce large-scale changes in the host microbiota composition and also to modulate the global metabolic function of the intestinal microbiome [20][21][22]. Probiotic DSM 17938 has been shown to have a mutualistic relationship between microbe and host [23][24][25].…”
Section: Introductionmentioning
confidence: 99%